2018
DOI: 10.1002/jcb.27774
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐10a functions as a tumor suppressor in prostate cancer via targeting KDM4A

Abstract: Deregulation of microRNAs contributes to the abnormal cell growth which is frequently observed in cancer. In the current study, we detected the expression and regulatory relationship between miR‐10a and Lysine‐specific demethylase 4A (KDM4A) to reveal their function in prostate cancer (PCa) progression. We found that miR‐10a levels were significantly decreased in PCa cell lines in comparison with the normal epithelial cell line RWPE‐1. Downregulation of miR‐10a levels was also observed in tumor tissues from PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…However, it should be noted that 25.5% (26 of 102) of all tumor specimens had high KDM4A expression but low USP1 expression (Figure 6D). Taken together, these results reveal that upregulation of USP1 expression could contribute to KDM4A overexpression in a substantial fraction of human prostate tumors, whereas in other prostate tumors, KDM4A can be activated by other posttranslational regulation, eg downregulation of microRNA‐10 was correlated with high expression levels of KMD4A in human prostate tumors 29 …”
Section: Resultsmentioning
confidence: 70%
“…However, it should be noted that 25.5% (26 of 102) of all tumor specimens had high KDM4A expression but low USP1 expression (Figure 6D). Taken together, these results reveal that upregulation of USP1 expression could contribute to KDM4A overexpression in a substantial fraction of human prostate tumors, whereas in other prostate tumors, KDM4A can be activated by other posttranslational regulation, eg downregulation of microRNA‐10 was correlated with high expression levels of KMD4A in human prostate tumors 29 …”
Section: Resultsmentioning
confidence: 70%
“…Our analysis of each differentially expressed miRNA in the cohort revealed that eight miRNAs likely arise as a result of false positive, driven by low number of reads in a limited number of samples while six are robust and not affected by any similar flaws. Published literature revealed that four of the six curated miRNAs, miR-1, miR-23b, miR-27a, and miR-27b, function as putative tumor suppressors that modulate proliferation and epithelial-mesenchymal transition in prostate and bladder cancer (30)(31)(32)(33)(34)(35)(36). The result portrays a mechanism that is consistent with literature in which tumor suppressor miRNAs are down-regulated during PCa progression (37).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, microRNA‐10a was reported to be in involved in the metastatic process by regulating EMT and hepatoma cell adhesion . In addition, miR‐10a functions as a tumor suppressor in prostate cancer via targeting KDM4A . Furthermore, miR‐10a could inhibit cell proliferation and promote cell apoptosis by targeting BCL6 in diffuse large B‐cell lymphoma …”
Section: Discussionmentioning
confidence: 99%